Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Recall the angle sum identities for cosine,
cos(x + y) = cos(x) cos(y) - sin(x) sin(y)
cos(x - y) = cos(x) cos(y) + sin(x) sin(y)
Now, by definition of tangent, we have
tan(x) = sin(x) / cos(x)
⇒ tan(44°) tan(46°) = sin(44°) sin(46°) / (cos(44°) cos(46°))
From the identities above, we can show that
cos(x) cos(y) = 1/2 (cos(x - y) + cos(x + y))
sin(x) sin(y) = 1/2 (cos(x - y) - cos(x + y))
so that
sin(44°) sin(46°) = 1/2 (cos(44° - 46°) - cos(44° + 46°))
⇒ sin(44°) sin(46°) = 1/2 (cos(-2°) - cos(90°))
⇒ sin(44°) sin(46°) = 1/2 cos(2°)
and
cos(44°) cos(46°) = 1/2 (cos(44° - 46°) + cos(44° + 46°))
⇒ cos(44°) cos(46°) = 1/2 (cos(-2°) + cos(90°))
⇒ cos(44°) cos(46°) = 1/2 cos(2°)
and in turn, it follows that
tan(44°) tan(46°) = (1/2 cos(2°)) / (1/2 cos(2°))
⇒ tan(44°) tan(46°) = 1
We have to prove that tan (44°) tan (46°) = 1 . So , for this we will use the sum identity for the tangent function i.e.
- [tex]{\boxed{\bf{\tan (x+y)=\dfrac{\tan (x)+\tan (y)}{1-\tan (x)\tan (y)}}}}[/tex]
So , here , we can easily get the answer by just putting x = 44° and y = 46° but let's first re-write it and then simplify to get the term tan(x) tan (y) , so that the answer will be just equal to what the product of tan (x) and tan (y) equal to
[tex]{:\implies \quad \sf \tan (x+y)\{1-\tan (x)\tan (y)\}=\tan (x)+\tan (y)}[/tex]
[tex]{:\implies \quad \sf 1-\tan (x)\tan (y)=\dfrac{\tan (x)+\tan (y)}{\tan (x+y)}}[/tex]
[tex]{:\implies \quad \sf \tan (x)\tan (y)=\dfrac{\tan (x)+\tan (y)}{\tan (x+y)}+1}[/tex]
Now , put x = 44° and y = 46°
[tex]{:\implies \quad \sf \tan (44^{\circ})\tan (46^{\circ})=\dfrac{\tan (44^{\circ})+\tan (46^{\circ})}{\tan (44^{\circ}+46^{\circ})}+1}[/tex]
[tex]{:\implies \quad \sf \tan (44^{\circ})\tan (46^{\circ})=\dfrac{\tan (44^{\circ})+\tan (46^{\circ})}{\tan (90^{\circ})}+1}[/tex]
[tex]{:\implies \quad \sf \tan (44^{\circ})\tan (46^{\circ})=\dfrac{\tan (44^{\circ})+\tan (46^{\circ})}{\infty}+1\quad \qquad \{\because \tan (90^{\circ})=\infty\}}[/tex]
[tex]{:\implies \quad \sf \tan (44^{\circ})\tan (46^{\circ})=0+1}[/tex]
[tex]{:\implies \quad \bf \therefore \quad \underline{\underline{\tan (44^{\circ})\tan (46^{\circ})=1}}}[/tex]
Hence , Proved
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.